Peran Ekonomi Digital Terhadap Ketahanan dan Pertumbuhan Ekonomi di Indonesia - Abdillah Arif Nasution; Tirsa Neyatri Bandrang; Dewi Mariam Widiniarsih; Muhammad Syaiful; Abdul Razak Munir (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the role of the digital economy in economic resilience and growth in Indonesia. This research approach collects data through literature studies, which involve reading literature from various sources including books, journals and reports using qualitative and deductive approaches. The findings in this study are. The potential of the digital economy greatly influences the resilience and growth of the Indonesian economy, this is able to make Indonesia the largest digital economy market share. The existence of the digital economy is greatly felt by the community, forcing related parties to design new strategies by adopting digitalization, which is dominated by innovation in technology, information, communication, and the increasing development of internet networks. The digital economy has a very important role in economic resilience and growth in Indonesia. Some of these roles include increasing efficiency and productivity, expanding markets, creating new jobs, and increasing innovation.